2018
DOI: 10.5731/pdajpst.2018.008664
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study to Address a Gap in the Device-to-Vial Interface Stopper Push-in by Chemo Spikes

Abstract: This case study is the first to address the risk, at the device-to-vial interface, of a spike pushing a stopper into a vial. It was performed after healthcare workers at cancer care hospitals complained about the risk of possible exposure to hazardous injectable drugs during the transfer if the spike pushed the stopper into the vial. This case study took a three-step approach to understand the device-to-vial interface, and the factors that determine stopper push-in force threshold and spike puncture force, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The force required to push the spike through the stopper increases as the stopper thickness increases. 16 This investigation highlights the importance of proper site training and technique to reduce the risk to vial wastage. Other challenges in relation to stopper coring and intrusion include leakage, breakage of vials, user fatigue and hand injuries.…”
Section: Product-agnostic Challengesmentioning
confidence: 85%
See 2 more Smart Citations
“…The force required to push the spike through the stopper increases as the stopper thickness increases. 16 This investigation highlights the importance of proper site training and technique to reduce the risk to vial wastage. Other challenges in relation to stopper coring and intrusion include leakage, breakage of vials, user fatigue and hand injuries.…”
Section: Product-agnostic Challengesmentioning
confidence: 85%
“…Additionally, West Pharmaceutical Services has conducted a thorough root cause analysis to understand the factors that lead to stopper intrusion, where the stopper is pushed into the vial, including puncture force, spike diameter, puncture location, and stopper thickness. 16 West concluded that the highest risk of stopper intrusion occurs when the spike puncture is misaligned with the center of the stopper. The force required to push the spike through the stopper increases as the stopper thickness increases.…”
Section: Product-agnostic Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other risks associated with CSTD use may include possible lubricants and leachables, 4,5 stopper coring/fragmentation, 6 and stopper push-in. 7 at the device-to-vial interface. Additionally, some CSTDs may contribute to dose inaccuracy, in cases where the device design and/or hold-up volume prevents complete withdrawal of the product from the primary DP container and/or transfer of the dose into the infusion container.…”
Section: Introductionmentioning
confidence: 99%
“…Issues with stoppers, especially stoppers being pushed in for vials containing lyophilized formulations, were also noted as a challenge. A recent report by Zhao et al 7 emphasized the need for device and drug developers to properly select and test stoppers and containers with intended spikes to prevent stopper push in from occurring. Petoskey et al 8 recently reported the complexities of CSTDs, especially in terms of lubricants, with an antibody drug conjugate.…”
mentioning
confidence: 99%